2020
DOI: 10.21082/bulpa.v18n2.2020.p113-122
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Keragaman Genetik dan Kekerabatan Genotipe Ubi Jalar Berdasarkan Karakter Morfologi

Abstract: Ubi jalar (Ipomoea batatas (L.) Lam.) merupakan komoditas sumber karbohidrat setelah padi, jagung dan ubi kayu. Saat ini produktivitas ubi jalar nasional hanya sebesar 13,51 t/ha, lebih rendah dibandingkan  hasil penelitian yang mencapai 35 t/ha. Penelitian ini bertujuan untuk mengevaluasi karakter morfologi beberapa genotipe ubi jalar dan menganalisis jarak genetik genotipe-genotipe berdasarkan karakter kuantitatif. Hasil analisis kekerabatan dari 13 genotipe ubi jalar berkelompok pada 2 klaster (A dan B). Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…The results of Prayudha et al ( 2019) obtained the Predominant vine color, the type of lobe, the lobes number, the leaf lobes shape, the type of plant, the size and length of the petiole, tubers per plant number, the tuber length, the tuber diameter, the internodes diameter, and internodes length have major contributions to the diversity of 11 purple sweet potato genotypes. Research by Lestari & Julianto (2020) showed that number of tubers, tuber weight, tuber dry matter, biomass dry matter, and harvest index were the characteristics that contributed greatly to the diversity of the 13 sweet potato genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Prayudha et al ( 2019) obtained the Predominant vine color, the type of lobe, the lobes number, the leaf lobes shape, the type of plant, the size and length of the petiole, tubers per plant number, the tuber length, the tuber diameter, the internodes diameter, and internodes length have major contributions to the diversity of 11 purple sweet potato genotypes. Research by Lestari & Julianto (2020) showed that number of tubers, tuber weight, tuber dry matter, biomass dry matter, and harvest index were the characteristics that contributed greatly to the diversity of the 13 sweet potato genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Hasil penelitian. Lestari & Julianto, (2020) menunjukkan 2 kelompok dendogram dari 13 genotipe dengan jarak Euclidean sebesar 0-0,25%.…”
Section: Analisis Tingkat Kemiripan 5 Genotipe Ubi Kayu Berdasarkan K...unclassified
“…Tiga belas genotipe yang dianalisis mempunyai keragaman genetik dan keragaman fenotipe yang luas terutama pada parameter jumlah umbi, bobot kering umbi, bobot kering brangkasan dan kadar betakaroten (Lestari & Julianto 2020). Tingginya nilai keragaman genetik dan keragaman fenotipe menjadikan kegiatan seleksi dalam proses pemuliaan tanaman untuk menghasikan varietas unggul akan berjalan lebih efektif dan efisien.…”
Section: Analisis Korelasiunclassified